An Exploratory Study of COVID-19’s Impact on Psychological Distress and Antisocial Behavior Among Justice-Involved Youth - Reid, Joan A. (Crime & delinquency, 2022)
Little is known about how justice-involved youth are coping with stress related to COVID-19. This study examined changes in psychological distress and antisocial behavior indicators among 557 youths on probation who completed two assessments during pre-COVID-19 conditions and two assessments during post-COVID-19 conditions. Drawing from Agnew?s General Strain Theory, the study used multivariate latent growth models to examine: (a) changes in psychological distress and antisocial behavior over time, (b) the associations of the changes, and (c) differences across sex, race, and ethnicity regarding changes in psychological distress. In support of General Strain Theory, results highlight that indicators of psychological distress and antisocial behavior increased during post-COVID-19 conditions when compared to pre-COVID-19 conditions for the full sample and for subsamples of youth categorized by sex, race, and ethnicity.